VARIASI PEMBERIAN BOKASHI PADA BUDIDAYA TANAMAN SAWI CAISIM (Brassica juncea L) DI DESA RANDUAGUNG KECAMATAN LAWANG KABUPATEN MALANG PROPINSI JAWA TIMUR - Latarus Fangohoi (JURNAL TRITON, 2016)
Mustard plants are very sensitive to environmental conditions that are less favorable, one important factor in the cultivation of mustard is knowing how many doses of fertilizer Bokashi right. This study aims to determine the dose Organic fertilizer per plant mustard right with a variety of fertilizers for growth and production of mustard (Brassica juncea L.). The experiment was arranged in the form of a randomized block design consisting of four treatments, P0 = without Bokashi fertilizer (control), P1 = 40 gr bokashi fertilizer / plant, P2 = 60 gr bokashi fertilizer / plant, P3 = 80 gr bokashi fertilizer / plant, and repeated 4 times. The parameters measured were (1) the plant height, (2) the number of leaves, (3) net weight of the plant. Observations of plant height and number of leaves of the plant since the plant was 7 days after planting up to 35 days, with intervals of observation time of 7 days. Observation of the net weight of the plant is done after the crop is harvested on day 35. The experimental results showed that the treatment dosages of P3 = 80 gr Bokashi gives the best results on the growth of plant height (42.75), the number of leaves of the plant (17 pcs) and net weight after harvest (185.50 g).